2016
DOI: 10.1007/s10290-016-0258-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of consuming imported cultural goods on trading partners’ tolerance toward immigrants: the case of Japanese anime in Korea

Abstract: The consumption of imported goods is thought to influence consumers' views and attitudes toward export countries. It is important to consider this issue especially when there is political tension and conflict between countries. Because of this historical background, political conflict exists between Korea and Japan. This paper examines the effect of viewing Japanese anime (animation) on the attitudes of Koreans toward Japanese living in Korea. The major findings of the study show that the more frequently adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In addition, Chinese people have had increased opportunity to travel and study abroad, which yields an opportunity for direct contact with foreign countries. Studies have found that exposure to foreign cultures promotes understanding of other countries, appreciation of diversity, and recognition of the importance of coexistence (Tulasiewicz 2015; Yamamura and Shin 2016). In the reform era, Chinese people pursued their interest in other countries, through learning foreign languages and following news from other countries, for instance.…”
Section: China's Involvement In the World And International Orientationsmentioning
confidence: 99%
“…In addition, Chinese people have had increased opportunity to travel and study abroad, which yields an opportunity for direct contact with foreign countries. Studies have found that exposure to foreign cultures promotes understanding of other countries, appreciation of diversity, and recognition of the importance of coexistence (Tulasiewicz 2015; Yamamura and Shin 2016). In the reform era, Chinese people pursued their interest in other countries, through learning foreign languages and following news from other countries, for instance.…”
Section: China's Involvement In the World And International Orientationsmentioning
confidence: 99%